A case report of drug rash with eosinophilia and systemic symptoms syndrome induced by dapsone - A. R., Swathy; Dattatri, A. N. (International Journal of Basic & Clinical Pharmacology, 2020)
Drug rash with eosinophilia and systemic symptoms (DRESS) syndrome is a distinct, severe, idiosyncratic reaction to a drug characterized by a prolonged latency period. It is followed by a variety of clinical manifestations, usually fever, rash, lymphadenopathy, eosinophilia, and a wide range of mild-to-severe systemic presentations. Among sulfonamides, Dapsone, sulfamethoxazole-trimethoprim and sulfasalazine are the most common offending drugs. We report here a case of DRESS syndrome due to dapsone.